Gait-Synchronized Rhythmic Brain Stimulation Improves Poststroke Gait Disturbance: A Pilot Study. Issue 11 (November 2019) - Koganemaru, Satoko; Kitatani, Ryosuke; Fukushima-Maeda, Ayaka; Mikami, Yusuke; Okita, Yusuke; Matsuhashi, Masao; Ohata, Koji; Kansaku, Kenji; Mima, Tatsuya
Abstract : Background and Purpose—: Gait disturbance is one of serious impairments lowering activity of daily life in poststroke patients. The patients often show reduced hip and knee joint flexion and ankle dorsiflexion of the lower limbs during the swing phase of gait, which is partly controlled by the primary motor cortex (M1). In the present study, we investigated whether gait-synchronized rhythmic brain stimulation targeting swing phase-related M1 activity can improve gait function in poststroke patients. Methods—: Eleven poststroke patients in the chronic phase participated in this single-blind crossover study. Each patient received oscillatory transcranial direct current stimulation over the affected M1 foot area and sham stimulation during treadmill gait. The brain stimulation was synchronized with individual gait rhythm, and the electrical current peaks reached immediately before initiation of the swing phase of the paretic lower limb. Ankle dorsiflexion was assisted by electrical neuromuscular stimulation in both real and sham conditions. Results—: Regarding the effects of a single intervention, the speed of self-paced gait was significantly increased after oscillatory transcranial direct current stimulation, but not after sham stimulation (paired t test, P =0.009). After we administered the intervention repeatedly, self- and maximally paced gait speed and timed up and go test performance were significantly improved (self-paced: F (1, 21) =8.91, P =0.007, maximally paced: F (1, 21) =7.09, P =0.015 and timed up and go test: F (1, 21) =12.27, P =0.002), along with improved balance function and increased joint flexion of the paretic limbs during gait. Conclusions—: These findings suggest that rhythmic brain stimulation synchronized with gait rhythm might be a promising approach to induce gait recovery in poststroke patients. Clinical Trial Registration—: URL: https://www.umin.ac.jp/ctr/ . Unique identifier: UMIN000013676. Abstract : Supplemental Digital Content is available in the text.